Teaching the Water Crisis as a Socio-Scientific Issue: A Didactic Proposal to Promote Critical Scientific Literacy - Villarroel Lobos, Cristopher Alexis (2026)
The water crisis constitutes one of the main socio-environmental challenges in Chile, exacerbated by structural factors such as water privatization, the pressure of large-scale productive projects, and the effects of climate change. In this context, science education can play a central role in fostering a critical and engaged citizenship in the face of socio-scientific issues. The present study aimed to evaluate the implementation of a didactic sequence within the subject Science for Citizenship, focused on the water crisis as a socio-scientific issue (SSI) and articulated with a pedagogical field trip to the Laguna de Tagua Tagua School Ecomuseum in the O’Higgins Region. The research was carried out under a qualitative case study approach, involving 65 third-year secondary students. Eight indicators of scientific literacy (SL) were designed, distributed across the three visions of SL. The results show that students achieved progressive advances in understanding fundamental concepts related to the water cycle, analyzing data on local rainfall and river flows, linking these to their everyday reality, and developing and communicating mitigation proposals regarding water scarcity, although with limitations in their implementation.